The diverse piscidin repertoire of the european sea bass (Dicentrarchus labrax): Molecular characterization and antimicrobial activities - Barroso, C (2020)
Fish rely on their innate immune responses to cope with the challenging aquatic environment, with antimicrobial peptides (AMPs) being one of the first line of defenses. Piscidins are a group of fish specific AMPs isolated in several species. However, in the European sea bass (Dicentrarchus labrax), the piscidin family remains poorly understood. We identified six different piscidins in sea bass, performed an in-depth molecular characterization and evaluated their antimicrobial activities against several bacterial and parasitic pathogens. Sea bass piscidins present variable amino acid sequences and antimicrobial activities, and can be divided in different sub groups: group 1, formed by piscidins 1 and 4; group 2, constituted by piscidins 2 and 5, and group 3, formed by piscidins 6 and 7. Additionally, we demonstrate that piscidins 1 to 5 possess a broad effect on multiple microorganisms, including mammalian parasites, while piscidins 6 and 7 have poor antibacterial and antiparasitic activities. These results raise questions on the functions of these peptides, particularly piscidins 6 and 7. Considering their limited antimicrobial activity, these piscidins might have other functional roles, but further studies are necessary to better understand what roles might those be.